2002
DOI: 10.1021/jo016257c
|View full text |Cite
|
Sign up to set email alerts
|

Role of NaBH4Stabilizer in the Oxazaborolidine-Catalyzed Asymmetric Reduction of Ketones with BH3-THF

Abstract: When stabilized BH(3-)THF (BTHF) was added to a mixture of ketone and tetrahydro-1-methyl-3,3-diphenyl-1H,3H-pyrrolo[1,2-c][1,3,2]oxazaborole (MeCBS-ozaxaborolidine, MeCBS) catalyst 1, low enantioselectivities resulted. Several relative rate experiments showed that a borohydride species in BTHF catalyzed the nonselective borane reduction of ketones, effectively competing with enantioselective MeCBS reduction of ketones, lowering the overall selectivity of the reaction. Improved enantioselectivities in the reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 20 publications
1
23
0
Order By: Relevance
“…Nettles et al reported that the NaBH 4 species in BH 3 ÁTHF participated in a non-selective uncatalyzed reduction that reduced the overall enantioselectivity (65% ee) of the CBS reduction of acetophenone compared to the high enantioselectivity of 95% ee when the non-stabilized BH 3 ÁTHF was used. 13 Therefore, in order to examine the role of NaBH 4 in the CBS reduction of trifluoromethyl ketone, we used the borane generated in situ from tetra-nbutylammonium borohydride (TBAB) and methyl iodide (MeI) 14 instead of the commercial nonstabilized borane. 15 Unfortunately, only a slight increase in selectivity was observed (entry 6).…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
See 2 more Smart Citations
“…Nettles et al reported that the NaBH 4 species in BH 3 ÁTHF participated in a non-selective uncatalyzed reduction that reduced the overall enantioselectivity (65% ee) of the CBS reduction of acetophenone compared to the high enantioselectivity of 95% ee when the non-stabilized BH 3 ÁTHF was used. 13 Therefore, in order to examine the role of NaBH 4 in the CBS reduction of trifluoromethyl ketone, we used the borane generated in situ from tetra-nbutylammonium borohydride (TBAB) and methyl iodide (MeI) 14 instead of the commercial nonstabilized borane. 15 Unfortunately, only a slight increase in selectivity was observed (entry 6).…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…These results imply that properly degraded BH 3 ÁTHF is superior to the NaBH 4 stabilized and non-stabilized BH 3 ÁTHF probably due to the by-produced butoxyborane species caused by the reduction of THF with BH 3 ÁTHF during storage, although this species had no effect on the enantioselectivity for the reduction of acetophenone. 13 Nettles et al also described that the addition of a Lewis acid removed or deactivated the borohydride (NaBH 4 ) in BH 3 ÁTHF and that the BF 3 ÁTHF complex (3-8 mol %) proved to be the best with a high enantioselectivity for the reduction of acetophenone among the examined Lewis acids (ZrCl 4 , AlCl 3 , FeCl 3 , and TiCl 4 ). 13 Fu et al simultaneously reported that the chemo-and enantioselectivities were dramatically enhanced by using an acid (BF 3 ÁOEt 2 and p-toluenesulfonic acid, 5 mol %) as a scavenger 16 for the NaBH 4 stabilizer in BH 3 ÁTHF for the reduction of a ketone with a chiral 4-phenyl-2-oxazolidinone auxiliary.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigations into the mechanism of the catalytic asymmetric reduction were also conducted [2,3]. Some researchers have paid much attention to the factors that affect the enantioselectivity in the asymmetric reduction, such as the structure [1,2,4], the stability [2a,5] and the loading amount [2a,5a,6] of catalysts, the type [7] and amount [2a,6c] of borane sources, the order and rate of the addition of a ketone or a borane complex into a reductive system [1d,6c], the reduction temperature [5d,6c,8], the solvent [5a,6c,7a,d], the additive [8g, 9,10], the secondary reduction [9a,11], the stabilizer in borane [12], the electronic effects of both ketones [4a,5a,10,13,14] and catalysts [4a,10,14], the kinetics of the asymmetric reduction [15], etc. Although some investigators have referred that different enantioselectivities could be observed with different borane sources [7], all of them evaluated the effect at about room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous new efficient oxazaborolidine catalysts have been reported, and a lot of applications have appeared until now [1]. In comparison with the numerous attempts to search for new catalysts to improve the enantioselectivity and to carry out the mechanistic investigation of the catalytic asymmetric reduction [2] [3], some investigators have studied the factors which affect the enantioselectivity in the asymmetric reduction, such as the structure [1] [2] [4], the stability [2a] [5] (including dimerization), and the loading amount [2a] [5a] [6] of the catalyst, the borane source [7] and amount [2a] [6c], the order and rate of the addition of a ketone or borane into a reductive system [1d] [10], the secondary reduction [9a] [11], the stabilizer in borane [12], the electronic effects of both ketones [4a] [5a] [10] [13] and catalysts [10] [14], etc. Although a few studies have dealt with the effects of the secondary reduction [9a] [11] and the additives [8g] [9] [10] on the enantioselectivity of the asymmetric reduction, these effects are still unclear.…”
mentioning
confidence: 99%